Pengaruh Belanja Pemerintah dan Pajak Daerah terhadap PDRB di 33 Kabupaten/Kota Provinsi Sumatera Utara - Purba, Bonaraja; Yolanda Putri br Hutasoit, Hosiana Febby; Ashari Siregar, Ilman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to analyze the effects of government spending and local taxes on GRDP in North Sumatra from 2016 to 2021. This study uses panel data analysis methods to determine the impact of independent variables on the dependent variable in 2016. panel data panel data analysis. the regression model after the Chow test and Hausman test showed that the effect model was still used. Based on t-statistic test (partial test). The probability values ​​of government spending and local taxes are 0.000 and 0.0000, so it can be concluded that the variables of government spending and local taxes have a significant effect on GRDP.